Clinical Presentation and Management of Multisystem Inflammatory Syndrome in Children With COVID-19: A Systematic Review - Albanji, Mohammed H; Baghafar, Ahmed A; Alghanmi, Yasser A; Shaaban, Mohammed M; Alkashlan, Ebrahim A; Sende, Haifa H; Alzahrani, Mofareh S; Filfilan, Nuha N (Curēus (Palo Alto, CA), 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a relatively new syndrome associated with coronavirus disease 2019 (COVID-19) that is characterized by a severe clinical course compared to pediatric COVID-19. This review aimed to compile the available evidence on the clinical presentation and management of MIS-C in children with COVID-19. During this systematic review, a comprehensive search was performed in the following databases: PubMed, Embase, Medline, Google Scholar, Cochrane, and Scopus, using predetermined search terms, such as Medical Subject Headings (MeSH) and keywords to find relevant studies on the MIS-C. Relevant data were extracted, and the quality of the studies was evaluated using suitable methods. The collected findings were synthesized and discussed in the study.The World Health Organization's (WHO) definition of MIS-C was the most favored due to its precision and inclusiveness. MIS-C primarily affected children aged 6-12 years, with male predominance. MIS-C involves a range of systems, including gastrointestinal, cardiovascular, hematologic, mucocutaneous, and respiratory. Radiographic findings revealed cardiovascular abnormalities, solid visceral organ involvement, and bowel abnormalities, reflecting a systemic inflammatory process. Laboratory investigations unveiled elevated inflammatory markers, neutrophil activation, release of extracellular traps in vessels, elevated procalcitonin, hyponatremia, hypoalbuminemia, low hemoglobin, and thrombocytopenia. The inflammatory markers and autoantibody profiles are essential in differentiating MIS-C from COVID-19. The preferred treatment primarily involves immunomodulatory therapies like intravenous immunoglobulin (IVIG), glucocorticoids, and interleukin-6 or 1RA inhibitors or a combination of those. In severe cases, extracorporeal membrane oxygenation (ECMO) and mechanical ventilation are necessary, leading to reduced mortality and quick recovery. This review found that the average hospital stay was seven days, and most discharged children fully recovered within seven days.MIS-C is a life-threatening post-COVID-19 condition and involves multiple systems due to systemic inflammation, with elevated inflammation markers. Recognition of multisystem involvement is crucial, and prompt identification and multidisciplinary treatment are vital for optimal outcomes.